Matriderm in depth-adjusted reconstruction of necrotising fasciitis defects - Ryssel, Henning; Germann, Günter; Czermak, Christoph; Kloeters, Oliver; Gazyakan, Emre; Riedel, Katrin (Burns, 2010)
Necrotising fasciitis (NF) and Fournier's gangrene are still a source of high morbidity and mortality and a significant health-care resource consumption. These difficult cases are increasingly being referred to burn centres for specialised wound and critical care issues. Besides the total body surface area (TBSA) affected, location, co-morbidities, age and an immediate surgical treatment are important prognostic factors. The treatment of these patients is challenging and best performed by prompt diagnosis, immediate radical surgical debridement and aggressive critical care management. Referral to a major burn centre may help provide optimal surgical intervention, wound care and critical care management.As soon as the patient is stabilised, reconstruction of the injured areas becomes the main focus. As often seen, complete loss of dermal structures needs a depth adjusted - ‘multilayer’ - reconstruction especially in critical areas. In modern reconstructive surgery, concepts of layer-specific reconstruction, including dermal substitution have to be considered. In this article, we present our recent experiences of five patients with NF who underwent dermal reconstruction with Matriderm® not only for better skin quality but also in some cases as an alternative to flap surgery when joint capsules or tendons were exposed.
Gesehen am 28.06.2023